2009
DOI: 10.1021/tx9000144
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Cross-Linking of Glutathione and Carnosine to Proteins by 4-Oxo-2-nonenal

Abstract: The lipid oxidation product 4-oxo-2-nonenal (ONE) derived from peroxidation of polyunsaturated fatty acids is a highly reactive protein cross-linking reagent. The major family of cross-links reflects conjugate addition of side-chain nucleophiles such as sulfhydryl or imidazole groups to the C=C of ONE to give either a 2- or 3-substituted 4-ketoaldehyde, which then undergoes Paal-Knorr condensation with the primary amine of protein lysine side-chains. If ONE is intercepted in biological fluids by antielectrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 47 publications
1
52
0
Order By: Relevance
“…We imagine a sequence involving first a Michael addition of glutathione to PL's more electrophilic C2-C3 olefin followed by the formation of a non-covalent complex between the PL-glutathione adduct and a glutathione-binding protein, and finally a Michael addition of a nucleophilic residue of the glutathione-binding protein to the less electrophilic C7-C8 olefin that is accelerated by the formation of the complex. Mechanistically analogous protein glutathionylation under conditions of electrophilic stress has been observed recently for the metabolic byproduct 4-oxo-nonenal (25) and the chemotherapeutic busulfan (26), both of which are bivalent electrophiles. Such a model also provides a chemical rationale for the results of an unbiased quantitative proteomics analysis of proteins binding to PL, which identified numerous glutathione-binding proteins among the highest confidence interactions (5).…”
Section: Discussionsupporting
confidence: 52%
“…We imagine a sequence involving first a Michael addition of glutathione to PL's more electrophilic C2-C3 olefin followed by the formation of a non-covalent complex between the PL-glutathione adduct and a glutathione-binding protein, and finally a Michael addition of a nucleophilic residue of the glutathione-binding protein to the less electrophilic C7-C8 olefin that is accelerated by the formation of the complex. Mechanistically analogous protein glutathionylation under conditions of electrophilic stress has been observed recently for the metabolic byproduct 4-oxo-nonenal (25) and the chemotherapeutic busulfan (26), both of which are bivalent electrophiles. Such a model also provides a chemical rationale for the results of an unbiased quantitative proteomics analysis of proteins binding to PL, which identified numerous glutathione-binding proteins among the highest confidence interactions (5).…”
Section: Discussionsupporting
confidence: 52%
“…Another possibility that could be considered was discovered for 4-oxo-2-nonenal (4-ONE) several years ago. This LPO product, once conjugated by GSH via Michael addition, was shown to effectively cross-link GSH to Lys residues of proteins, in the mentioned study shown for the model protein β-lactoglobulin (28). Although this is a plausible mechanism, not least due to the proven Schiff base formation of 2EHD and Lys ( Figure 4D), further clarification is needed.…”
Section: Discussionmentioning
confidence: 83%
“…The polyunsaturated lipid peroxidation product 4-oxo-2-nonenal (ONE) is a highly reactive protein cross-linking agent (Zhu, Gallogly, Mieyal, Anderson, & Sayre, 2009). The compound also adds to GSH, resulting in the formation of a reactive 4-ketoaldehyde that has the potential to covalently add to proteins (Cooper, Pinto, et al, 2011).…”
Section: Nonreducible Glutathionylation Involving Covalent Tetheringmentioning
confidence: 99%